Natural resource management and development discourses in the Caribbean : reflections on the Guyanese and Jamaican experience - Mistry, Jayalaxshmi (2009)
Describes the environment and development history of Guyana and Jamaica through pre-colonial, colonial, independence and market liberalisation stages.